PENGARUH SPECIAL EVENT KICKFEST TERHADAP PENGETAHUAN KHALAYAK MENGENAI BRAND LOKAL - Firdha Saskia Putri (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2016)
The purpose of this study was to determine the effect Kickfest special event in 2015 to the audience about the knowledge of local brands. Measurements were performed by measuring variables Kickfest event as the variables X and knowledge of the audience as a variable Y. There is no X variable dimensions measured is the intensity, style,content of media messages and media. Dimensions variable Y measured cognitive, affective and conative. The samples used were 100 respondents who came to the event Kickfest year 2015.Analisis used in this study is a quantitative analysis, analysis of Pearson product moment, normality test, regression analysis and determination test. The results of the research carried out showed that the respondent's assessment Kickfest event was very good. While the influence of special events between Kickfest against public knowledge gained r of 0.466 stating Kickfest special event and the knowledge of the audience showed a fairly strong relationship. Meanwhile, the results also showed the influence of special events for knowledge Kickfest audience is 21.7%.